Integrated solar fuel generators - Sharp, Ian D.; Atwater, Harry A. 1960-; Lewerenz, Hans-Joachim (Royal Society of Chemistry, 2019)
This book describes the critical areas of research and development towards viable integrated solar fuels systems, the current state of the art of these efforts and outlines future research needs.
Includes index.
Title from title details screen.
Keywords: Solar energy.; elektronické knihy; electronic books